Tamil Nadu Board of Secondary EducationSSLC (English Medium) Class 10th
Advertisement Remove all ads

If f(x) = 2x – 1, g(x) = x+12, show that fog = gof = x - Mathematics

Sum

If f(x) = 2x – 1, g(x) = `(x + 1)/(2)`, show that fog = gof = x

Advertisement Remove all ads

Solution

f(x) = 2x – 1, g(x) = `(x + 1)/(2)`

fog = f[g(x)]

= `"f"[(x + 1)/2] - 1`

= `2 [(x + 1)/2] - 1`

= x + 1 – 1

= x

gof = g[f(x)]

= g(2x – 1)

= `(2x - 1 + 1)/2`

= `(2x)/2`

= x

∴  fog = gof = x

Hence it is proved.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Samacheer Kalvi Mathematics Class 10 SSLC Tamil Nadu State Board
Chapter 1 Relations and Functions
Exercise 1.5 | Q 3 | Page 31
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×